Isolamento e caracterização de fungos endofíticos associados a Paspalum atratum Swallen e Paspalum notatum Fluggé com potencial biotecnológico e agrícola para promoção de crescimento vegetal e biocontrole - Pedrino, Isadora Camargo (Universidade Federal de São Carlos, 2023)
The genus Paspalum sp. participates in the composition of pastures throughout the American continent, being adapted to different environmental conditions. Paspalum atratum is a species that adapts to rough soils with low fertility and seasonally flooded. Paspalum notatum is a species adapted to dry soils, flooded soils, and soils with low fertility. Often found in disadvantageous situations, endophytic fungi may be responsible for assisting in the maintenance of vegetables, as these microorganisms reside inside plants, increasing resistance to abiotic and biotic stresses. The use of fungi with the ability to promote plant growth and carry out biocontrol are strategies to replace widely used chemical fertilizers, insecticides, and fungicides, as well as to meet the demands of plants in a more effective and sustainable way. The present study aimed to isolate and characterize endophytic fungi associated with P. atratum and P. notatum and to evaluate the inorganic phosphate solubilization potential (SFI) and the antagonistic potential against phytopathogens. Fungi were isolated from roots and leaves, and tested in vitro for SFI and antagonism against phytopathogenic fungi Bipolaris sp. and Colletotrichum sp. Among the 385 fungal isolates obtained, 213 solubilized inorganic phosphate and those that presented the best potential for SFI and antagonism against phytopathogens were identified. Identification was performed by sequencing the ITS region of ribosomal DNA, and the genera identified were Aspegillus sp., Colletotrichum sp., Fusarium sp., Microdochium sp., Neosartorya sp., Penicillium sp. and Phoma sp. as endophytes of P. atratum, and Aspegillus sp., Ceratobasidium sp., Colletotrichum sp., Curvularia sp., Fusarium sp., Microdochium sp., Penicillium sp. and Talaromyces sp. as endophytes of P. notatum.
Isolation and characterization of endophytic fungi associated with Paspalum atratum Swallen and Paspalum notatum Fluggé with biotechnological and agricultural potential for plant growth promotion and biocontrol
Keywords: Banco ativo de germoplasma; Controle biológico; Promoção de crescimento vegetal; Solubilização de fosfato inorgânico; Active germplasm bank; Biological control; Plant growth promotion; Inorganic phosphate solubilization; CIENCIAS AGRARIAS::AGRONOMIA::FITOSSANIDADE::MICROBIOLOGIA AGRICOLA